Odpowiedzi

2010-04-10T20:05:12+02:00
(1+ sinα) (1/cosα - 1/ctgα) - cosα = 0
L=(1+ sinα) (1/cosα - tgα) - cosα=(1+ sinα) (1/cosα - sinα/cosα) - cosα=
=(1+ sinα)((1- sinα)/cosα) - cosα=(1 - sin²α)/cosα - cosα= cos²α/cosα - cosα=
cosα - cosα=0=P
2010-04-10T20:06:08+02:00
Rozwiązanie w załączniku
:-)))
2010-04-10T20:09:07+02:00
Sprawdź tożsamość:
(1+ sinα) (1/cosα - 1/ctgα) - cosα = 0
L=1/cosα-1/ctgα+sinα/cosα-sinα/ctgα-cosα=
1/cosα-tgα+tgα-sinα/ctgα-cosα=1/cosα-sinα/(cosα/sinα)-cosα=
1/cosα-sin²α/cosα-cosα=(1-sin²α)/cosα-cosα=cos²α/cosα-cosα=0=P